Religion in Early Stuart England, 1603–1638: An Anthology of Primary Sources. Edited by Debora Shuger - Hampton, Stephen (The journal of theological studies, 2014)
This is a rich and thought-provoking collection of primary sources. Professor Shuger indicates in her introduction that she had three principal aims in mind when compiling it. She intended, first, ‘to elucidate the central theological creeds and controversies of the era’; second, ‘to capture something of the variety of religious expression’; and third, ‘to recover forgotten works of unusual beauty, intelligence, or simply interest’. She has certainly succeeded in her second and third aims, which is why her book is a welcome contribution to the field. She presents somewhat over fifty texts from the early Stuart period, drawn from a wide range of authors, written for a wide variety of contexts, and representing a range of literary genres.